If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 65 = 115 Reorder the terms: 65 + 4x = 115 Solving 65 + 4x = 115 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-65' to each side of the equation. 65 + -65 + 4x = 115 + -65 Combine like terms: 65 + -65 = 0 0 + 4x = 115 + -65 4x = 115 + -65 Combine like terms: 115 + -65 = 50 4x = 50 Divide each side by '4'. x = 12.5 Simplifying x = 12.5
| 54-88= | | 1/4(-2)-1 | | 30=(13/2)*h | | -2x-16=-38 | | 3x+x+3x+x=1000 | | 30=(13/2)h | | 0.6x+1.2=33 | | 13=-x/4+15 | | 10=e/4+3 | | -35=-15-x/3 | | 4x+0=12 | | 1/4*-2-1 | | -9-47= | | -24=-32-x/2 | | 1/4x-2-1 | | 2-5x=-3 | | 2x+2-9=-15 | | 3x=15x-84 | | -2*-0+1= | | -2*-1+1= | | 1/4x-1 | | -6-2y=6 | | 32-(-16)= | | -2*-2+1= | | -35=-5d | | -2*-3+1= | | y=(3)/(5x-7) | | 2x+(1)=-8 | | 22-(-3)= | | Y=(3)/5x-7 | | 8y+y^2+25=0 | | x^2+16x+41=0 |